FEATURES OF MONETARY POLICY OF UKRAINE IN MODERN CONDITIONS - Харабара, Віолетта; Грешко, Роман Ігорович; Третякова, Олена Василівна (Kharabara V., Greshko R., Tretyakova O. Features of monetary policy of Ukraine in modern conditions. The XI th International scientific and practical conference «Academic research in multidisciplinary innovation» November 30 - December 03, 2020. Amsterdam, Netherlands . - Pp.51-55., 2020)
The aim of the study was to determine the features of monetary policy in Ukraine at the present stage. Attention is paid to the practice of implementing the inflation targeting regime and the peculiarities of its implementation. The experience of managing the level of the key interest rate of the central bank as the main tool for achieving internal equilibrium is considered; the dynamics of the interest rate and its relationship with other economic processes are analyzed. The main threats and shortcomings of the NBU's current monetary policy, which stand in the way of effective monetary regulation, have been identified. In particular, issues such as high levels of uncertainty, significant dollarization of the economy, exchange rate instability and hryvnia devaluation, low levels of gold and foreign exchange reserves, the problem of refinancing commercial banks and the NBU's policy on IGLBs were considered. Solving these problems will be important prerequisites for an effective monetary policy in Ukraine.
Keywords: monetary policy; inflation targeting; the level of monetization of the economy